2019
DOI: 10.1002/anie.201908649
|View full text |Cite
|
Sign up to set email alerts
|

From Bad Electrochemical Practices to an Environmental and Waste Reducing Approach for the Generation of Active Hydrogen Evolving Electrodes

Abstract: The electrodeposition of noble metals using corresponding dissolved metal salts represents an interesting process for the improvement of the electrocatalytic hydrogen evolution reaction (HER) properties of less active substrate materials. The fact that only a small fraction of the dissolved noble metals reaches the substrate represents a serious obstacle to this common procedure. We therefore chose a different path. It was found that the HER activity of Ni42 alloy drastically increased (η=140 mV at j=10 mA cm−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 66 publications
1
25
0
Order By: Relevance
“…This is to be expected as Pt is a far more efficient electrocatalyst for the HER than Au. This is consistent with previous work where it was shown that Pt decoration of Ni42 steel also resulted in excellent HER activity [34] …”
Section: Resultssupporting
confidence: 93%
“…This is to be expected as Pt is a far more efficient electrocatalyst for the HER than Au. This is consistent with previous work where it was shown that Pt decoration of Ni42 steel also resulted in excellent HER activity [34] …”
Section: Resultssupporting
confidence: 93%
“…Encouraged by the initial HER cycling tests, the electrochemical performance of PdNP@GNF was tested over a larger number of cycles, up to 30000 cycles, and compared with that of the Pt/C electrocatalyst benchmark after 5000 and 30000 cycles under the same conditions (Figure 3 c,d and Figure 4 ). It is worth noting that accelerated durability tests were carried out using a carbon counter electrode, which rule out Pt dissolution‐redeposition effects[ 54 , 55 , 56 ] on the observed electrochemical performance. It is remarkable that as the number of HER cycles increases, the performance of the PdNP@GNF catalyst continues to improve, overtaking Pt/C after about 15000 cycles (Table 1 and Figure 4 c).…”
Section: Electrocatalysis Of the Her In Pdnp@gnf Nanoreactorsmentioning
confidence: 99%
“…Hydrogen is an ideal renewable energy resource because it has the highest energy density per mass and is easy to burn without release of pollutants. [1][2][3][4][5] Water splitting is a green approach for hydrogen production that be used for energy storage of intermittent sources such as solar or wind in the form of fuels. [6][7][8][9][10][11] Hydrogen evolution reaction (HER) is one of two half reactions in water splitting that requires a catalyst to reduce the overpotential.…”
Section: Introductionmentioning
confidence: 99%